Flow‐Dependence of Ensemble Spread of Subseasonal Forecasts Explored via North Atlantic‐European Weather Regimes - Spaeth, J.; Rupp, P.; Osman, M.; Grams, C. M.; Birner, T. (John Wiley and Sons, 2024)
Atmospheric prediction at 2–6 weeks lead time (so-called subseasonal-to-seasonal timescales) entails large forecast uncertainty. Here we investigate the flow-dependence of this uncertainty during Boreal winter. We categorize the large-scale flow using North Atlantic-European weather regimes. First, we show that forecast uncertainty of near-surface geopotential height (Z1000) and temperature (T2m) are strongly sensitive to the prevailing regime. Specifically, forecast uncertainty of Z1000 reduces over northern Europe following Greenland Blocking (enhanced predictability) due to a southward shifting eddy-driven jet. However, due to strong temperature gradients and variable flow patterns, Greenland blocking is linked to increased forecast uncertainty of T2m over Europe (reduced predictability). Second, we show that forecast uncertainty of weather regimes is modulated via the stratospheric polar vortex. Weak polar vortex states tend to reduce regime-uncertainty, for example, due to more frequent predicted occurrence of Greenland blocking. These regime changes are associated with increased T2m uncertainty over Europe.